Pengaruh Metode Video Based Learning terhadap Pengetahuan Menyikat Gigi pada Siswa/I Kelas IV dan V di SD Negeri 71 Banda Aceh - Muhammad Bayta’wi; Syukriadi Syukriadi; Pasyamei Rembune Kala (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Brushing teeth among elementary school students continues to be a concern for everyone, especially in maintaining their dental health. To generate the level of the students’ knowledge, it can be seen from a video-based learning method. The survey in SD Negeri 71 Banda Aceh showed that most students have a misunderstanding of how to do proper brushing of teeth. The other way to monitor mouth health is to have never watched educational media in the form of videos. This study aims to determine the video-based learning method on tooth brushing knowledge among fourth and fifth-grade students of SD Negeri 71 Banda Aceh. This study is a quantitative study using a correlational approach with quasi quasi-experimental design of Pre-Test and Post-Test. This study consisted of one group that examined the knowledge using the instrument of video therapy. The sample was 45 students that never chosen by using a total sampling technique of all population. Data analysis using univariate and bivariate analyses with a normality test and the Wilcoxon Signed Rank Test. The findings indicate that knowledge with Cronbach's Alpha (0.758) > r table (0,361) and video-based learning. The result of the bivariate analysis obtained the average statistical value for the pretest as 157. The calculation for the post-test value is 170 with a p-value = 0,000 (≤ 0.05). Therefore, this study proves that there is an effect of the video-based learning method on tooth brushing knowledge of fourth and fifth-grade students in SD Negeri 71 Banda Aceh. It is expected that students can apply the information provided on brushing their teeth in daily life.